Characterization of donut-like SrMoOproduced by microwave-hydrothermal process - Wannapop S. (2014)
SrMoO4 hierarchical nanostructures were successfully produced by a one step of 270 W microwave-hydrothermal process of one of the solutions containing three strontium salts [Sr(NO3)2, Sr(CH 3CO2)2, and SrCl2·6H 2O] and (NH4)6Mo7O 24·4H2O for different lengths of time. The as-produced products were characterized by X-ray diffraction, electron microscopy, and spectroscopy. In this research, they were primitive tetragonal structured donut-like SrMoO4, with the main 881 cm - 1 1 (A g) symmetric stretching vibration mode of [ MoO4]2- units and 3.92 eV energy gap. © 2013 Surangkana Wannapop et al.